2019
DOI: 10.3390/f10121063
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Production Forests for Sustaining Lichen Diversity: A Perspective on Sustainable Forest Management

Abstract: There is a critical gap in our knowledge about sustainable forest management in order to maintain biodiversity with respect to allocating conservation efforts between production forests and set-asides. Field studies on this question are notably scarce on species-rich, poorly detectable taxon groups. On the basis of forest lichen surveys in Estonia, we assessed the following: (i) how much production stands contribute to maintaining the full species pool and (ii) how forest habitat conditions affect this contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 83 publications
0
16
0
2
Order By: Relevance
“…In analyses on lichenized and wood-inhabiting fungi, we have concluded that focal-species criteria can be met in ca. 2% of the Estonian forest species pool [92,93]. This points at an order of magnitude of a few hundred focal species to be considered for forestry in this country.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In analyses on lichenized and wood-inhabiting fungi, we have concluded that focal-species criteria can be met in ca. 2% of the Estonian forest species pool [92,93]. This points at an order of magnitude of a few hundred focal species to be considered for forestry in this country.…”
Section: Discussionmentioning
confidence: 96%
“…For example, forest fungal surrogates have been explored in many studies [90], including the matching of selected wood-inhabiting species with threats [91,92]. Specialized lichens appear suitable for guiding multiple management dimensions [93], but spatial models for that remain scarce (Table 1). Modeling for decision-making may have thus contributed to the taxonomic bias in SFM, which is usually attributed to insufficient stakeholder knowledge [94].…”
Section: Published Spatial Models Of Focal Species Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a criterion for site selection was the availability of earlier (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) information (e.g. Andersson et al, 2003;Lõhmus & Lõhmus, 2019;Runnel & Lõhmus, 2017).…”
Section: Study Area and Designmentioning
confidence: 99%
“…Papers by Re ňco et al [5] and Lõhmus and Lõhmus [6] document species diversity of species-rich, but understudied species in Eastern European forests. Re ňco et al studied the response of soil nematodes and microbial communities to windstorms in beech and spruce forests.…”
mentioning
confidence: 99%